Distribution service performance optimization of PDAM Tirta Taman Bontang City East Kalimantan Province - Wahyu Nugraha, Aviantara; Anwar, M. Ruslin; Suryo, Eko Andi (Fakultas Teknik Universitas Brawijaya, 2023)
To achieve the level of service performance from PDAM Tirta Taman Kota Bontang, obtained based on user perceptions of PDAM Taman Tirta obtained from the results of a questionnaire with a Likert scale using the Importance Performance Analysis (IPA) method. From the IPA analysis results, interviews were conducted using the Strength, Weakness, Opportunities, Threats (SWOT) method. The results of the IPA analysis were used in quadrant I, namely service to the registration process (x11), the survey of prospective customer locations (x12), time of survey implementation (x13), Payment orders before installation (x15), Notice the length of the installation process (X15). Registration up to installation (X16), the supplied water meets health standards, attributes (X21 ), the quality of the supplied water (color, smell, taste) (X22), report to PDAM Tirta Taman if there is a disturbance or it doesn't work smoothly (x 33 ), the duration of handling the damage house connection (x 43 ), customer or prospective customer database of PDAM Tirta Taman (x 71 ). Then the SWOT quadrant matrix with the SO ( Strengths-Opportunities ) strategy, namely development with IT and social media Periodic pipe rejuvenation to avoid pipe leaks that can affect quality, Providing Customer Service via WhatsApp for service notifications, disruptions and payment orders, Issuing SOPs new and regular schedule for maintenance. Continue to perform security updates on the database storage system. Use official forms for prospective customers interested in installing a new connection. Keywords: PDAM Taman Tirta, Validity Test, Reliability Test, Service Performance, Importance Performance Analysis, SWOT